Genome-Wide Scans for Ghanaian Plasmodium falciparum Genes Under Selection From Local and Chinese Host Populations - Shi, Shan-Mei; Shi, Tian-Qi; Chen, Shen-Bo; Cui, Yan-Bing; Kassegne, Kokouvi; Okpeku, Moses; Chen, Jun-Hu; Shen, Hai-Mo (Frontiers in Cellular and Infection Microbiology, 2021)
Humans with no previous exposure to malaria almost invariably become ill when exposed to the parasite. Infection that is not fatal, essentially, induces complete protection from severe illness and death. However, because immunity is acquired through constant exposure to the parasite, with the decrease in transmission around the world, comes growing concerns about declining immunity in communities and a shift towards greater susceptibility to symptomatic disease. To test for selection that might occur due to varying patterns of transmission level, varying antimalarial drug use, or other causes, Plasomdium falciparum clinical samples from Chinese hosts who worked in Ghana were whole-genome sequenced (WGS) and compared with the WGS data of isolates from native Ghanaian downloaded from pf3k. The P. falciparum samples clustered generally according to their geographic origin, and Chinese imported samples showed clear African origin with slightly different distribution with Ghana local samples. Against the background of similar structure, samples collected from two host populations showed evidence indicating differences in intensity of selection. Compared with Ghana local samples, the China imported isolates exhibited higher proportion of monoclonal infections, and lots of genes associated with RBC invasion and immune evasion are under lower level selection pressures. There was no significant difference on selection of drug-resistance genes due to similar Artemisinin-based combination therapy (ACT) based medication profile. Locally varying selection on parasites may be due to differences in host immunity or transmission opportunities between hosts. In China most P. falciparum infections were imported from Africa, and gene flow is relatively unrestricted in this case, but markedly varying acquired immunity and transmission intensity should cause distinct local selective pressures. This study revealed the impact of host switching on natural immunity, and may provide a better understanding of the mechanisms by which natural immunity to malaria is achieved.